Role of Coagulation Inhibitors in Inflammation - Esmon, Charles T. (Thrombosis and Haemostasis, 2001)
It is becoming increasingly clear that coagulation augments inflammation and that anticoagulants, particularly natural anticoagulants, can limit the coagulation induced increases in the inflammatory response. The latter control mechanisms appear to involve not only the inhibition of the coagulation proteases, but interactions with the cells that either generate anti-inflammatory substances, such as prostacyclin, or limit cell activation. Recent studies have demonstrated a variety of mechanisms by which coagulation, particularly the generation of thrombin, factor Xa and the tissue factor-factor VIIa complex, can augment acute inflammatory responses. Many of these responses are due to the activation of one or more of the protease activated receptors. Activation of these receptors on endothelium can lead to the expression of adhesion molecules and platelet activating factor, thereby facilitating leukocyte activation. Therefore, anticoagulants that inhibit any of these factors would be expected to dampen the inflammatory response.The three major natural anticoagulant mechanisms seem to exert a further inhibition of these processes by impacting cellular responses. Antithrombin has been shown in vitro to increase prostacyclin responses and activated protein C has been shown to inhibit a variety of cellular responses including endotoxin induced calcium fluxes in monocytes and the nuclear translocation of NFκB, a key step in the generation of the inflammatory response. In some, but not all, in vivo models, these natural anticoagulants have been able to inhibit endotoxin/E. colimediated leukocyte activation and to diminish cytokine elaboration (TNF, IL-6 and IL-8). Phase III clinical studies for treatment of patients with severe sepsis have been completed for APC, which was successful (1), and for antithrombin, which was not (2). A phase III trial with tissue factor pathway inhibitor is in progress. In this review, the mechanisms by which the different natural anticoagulants are thought to function will be reviewed.
Keywords: Thrombin; natural anticoagulants; inflammation; sepsis; endothelium